Globalization and Labour in China and India
XIV, 271 p.
Keywords: Globalization has pushed China and India to the centre of the stage but what has been the impact on workers in these countries? This book demonstrates the complexity of the processes and responses at play. There are signs that both states are shifting their role in a 'counter movement from above'. But will this be enough to quell the social unrest?